Evaluating the E-Learning on Students' Character: Blended Learning Model as a Strategy to Improve Students' Character. (February 2019) - Wardani, F; Suparmi,; Aminah, N S
Abstract: This study aims to evaluate E-learning towards the achievement of students' character and determine strategies to build students' character through the use of e-learning. The subjects in this study were 132 students of grade X of the SragenVocational School. The data in this study are quantitative data and qualitative data. Quantitative data is obtained from the results of self-assessment questionnaires by students. Qualitative data were obtained based on the results of the interview by students as supporting self-assessment questionnaire result. The self-assessment questionnaire consisted of 6 aspects of character, namely 1) Friendly and Responsibility, 2) Religious and living in harmony, 3) Honesty, 4) Creative and Curiosity, 5) Tolerance, and 6) Discipline. The results showed that the percentages of achievement of the students' character are; friendly and responsibility (63.2%), religious and living in harmony (73.9%), honesty (64.4%), creative and curiosity (61.6%), tolerance (72.9%), and discipline (68.8%). The data shows that the percentage of student characters was still low. One strategy which can be used to build students' character is through the use of e-learning by applying blended learning models.